Longitudinal links between expressive flexibility and friendship quality in adolescence: The moderating effect of social anxiety. Issue 3 (22nd November 2022) - Wang, Yingqian; Hawk, Skyler T.; Branje, Susan; Van Lissa, Caspar J.
Abstract: Introduction: Expressive flexibility, or the ability to both up‐ and down‐regulate emotional expressions in social interactions, is thought as an indicator and a consequence of healthy interpersonal relationships. The present longitudinal study examined bidirectional associations between expressive flexibility and friendship quality in early adolescence. Since prior research found inconsistent results regarding the adaptiveness of expressive flexibility, which indicated the necessity to consider individual variability in the process, we further tested the potential moderating effect of social anxiety in the links from expressive flexibility to friendship quality. Methods: Participants from two junior high schools in eastern China ( N  = 274; 50.4% female; M age  = 13.56) were surveyed at three time points with 6‐month intervals. Expressive flexibility, friendship quality, and social anxiety were all assessed via self‐reported scales. Results: According to the cross‐lagged model results, friendship quality significantly predicted increased expressive flexibility over time. Conversely, the longitudinal association from expressive flexibility to friendship quality was not significant, but the interaction between expressive flexibility and social anxiety significantly predicted later friendship quality. Further analyses via the Johnson–Neyman technique revealed that expressive flexibility only positively predicted friendship quality for adolescents with lower levels of social anxiety. Conclusion: Our results suggest that expressive flexibility is not always socially adaptive, so practical interventions that aim to improve youths' social adjustment via expressive flexibility training might need to consider the role of individual characteristics.